Perinatal exposure to foodborne inorganic nanoparticles: A role in the susceptibility to food allergy? - Issa, Mohammad; Rivière, Gilles; Houdeau, Eric; Adel-Patient, Karine (Frontiers in Allergy, 2022)
Food allergy (FA) is an inappropriate immune response against dietary antigens. Various environmental factors during perinatal life may alter the establishment of intestinal homeostasis, thereby predisposing individuals to the development of such immune-related diseases. Among these factors, recent studies have emphasized the chronic dietary exposure of the mother to foodborne inorganic nanoparticles (NP) such as nano-sized silicon dioxide (SiO2), titanium dioxide (TiO2) or silver (Ag). Indeed, there is growing evidence that these inorganic agents, used as food additives in various products, as processing aids during food manufacturing or in food contact materials, can cross the placental barrier and reach the developing fetus. Excretion in milk is also suggested, hence continuing to expose the neonate during a critical window of susceptibility. Due to their immunotoxical and biocidal properties, such exposure may disrupt the host-intestinal microbiota's beneficial exchanges and may interfere with intestinal barrier and gut-associated immune system development in fetuses then the neonates. The resulting dysregulated intestinal homeostasis in the infant may significantly impede the induction of oral tolerance, a crucial process of immune unresponsiveness to food antigens. The current review focuses on the possible impacts of perinatal exposure to foodborne NP during pregnancy and early life on the susceptibility to developing FA.